Pengembangan Oobii Cheesecake Bebas Gluten Berbasis Ubi Ungu Sebagai Alternatif Dessert Fungsional - Kezia Elsty; Christopher Jason; Celine Van Der Leer (Politeknik Bosowa, 2026)
The increasing awareness of gluten intolerance and celiac disease has encouraged the development of gluten-free food products that maintain nutritional value and consumer acceptability. This study aims to develop and analyze the nutritional potential of gluten-free Oobii Cheesecake as an alternative functional dessert. The research was conducted using an experimental method by formulating a cheesecake product with gluten-free ingredients. Nutritional analysis was performed to evaluate the macronutrient content, including energy, carbohydrates, protein, and fat. The formulation process focused on achieving acceptable texture, taste, and overall product quality while eliminating gluten-containing components. The results indicated that gluten-free Oobii Cheesecake provides balanced macronutrient composition and adequate energy content, making it suitable as a dessert option for individuals with gluten intolerance. In addition, the product demonstrated potential as a functional food due to its nutritional profile and adaptability to healthydietary patterns. In conclusion, gluten-free Oobii Cheesecake can be considered a promising innovation in gluten-free dessert development and may serve as a safe and nutritious alternative for consumers seeking gluten-free food products. Keyword : gluten-free, cheesecake, functional food, nutritional value, healthy dessert